Mediation : positive conflict management - Haynes, John M. (SUNY series in transpersonal and humanistic psychology., 2004)
"This mediation how-to manual brings together the collective wisdom of two of the field's most renowned founders, John Michael Haynes and Larry Sun Fong. The book not only covers a range of mediation cases, but also uniquely provides feedback from the clients as they reflect on the sessions and report on what worked best for them."--Jacket